Evidence for in vitro and in vivo activity of the antimalarial pyronaridine against Schistosoma. - Erik Koehne; Nina Zander; Miriam Rodi; Jana Held; Wolfgang Hoffmann; Rella Zoleko-Manego; Michael Ramharter; Ghyslain Mombo-Ngoma; Peter G Kremsner; Andrea Kreidenweiss (Public Library of Science (PLoS), 2021)
Background Schistosomiasis is highly prevalent in Africa. Praziquantel is effective against adult schistosomes but leaves prepatent stages unaffected-which is a limit to patient management and elimination. Given the large-scale use of praziquantel, development of drug resistance by Schistosoma is feared. Antimalarials are promising drugs for alternative treatment strategies of Schistosoma infections. Development of drugs with activity against both malaria and schistosomiasis is particularly appealing as schistosome infections often occur concomitantly with malaria parasites in sub-Saharan Africa. Therefore, antiplasmodial compounds were progressively tested against Schistosoma in vitro, in mice, and in a clinical study. Results Amongst 16 drugs and 1 control tested, pyronaridine, methylene blue and 5 other antimalarials were highly active in vitro against larval stage schistosomula with a 50% inhibitory concentration below 10 μM. Both drugs were lethal to ex vivo adult worms tested at 30 μM with methylene blue also active at 10 μM. Pyronaridine treatment of mice infected with S. mansoni at the prepatent stage reduced worm burden by 82% and cured 7 out of 12 animals, however in mice adult stages remained viable. In contrast, methylene blue inhibited adult worms by 60% but cure was not achieved. In an observational pilot trial in Gabon in children, the antimalarial drug combination pyronaridine-artesunate (Pyramax) reduced S. haematobium egg excretion from 10/10 ml urine to 0/10 ml urine, and 3 out of 4 children were cured. Conclusion Pyronaridine and methylene blue warrant further investigation as candidates for schistosomiasis treatment. Both compounds are approved for human use and evidence for their potential as antischistosomal compounds can be obtained directly from clinical testing. Particularly, pyronaridine-artesunate, already available as an antimalarial drug, calls for further clinical evaluation. Trial registration ClinicalTrials.gov Identifier NCT03201770.